Growth and Productivity of Short Duration Aman Rice Genotype (Bangladesh Agronomy Journal, 2018)
A field experiment was conducted at the research field of Agronomy Department of Bangabandhu Sheikh Mujibur Rahman Agricultural University during Aman season of 2014. Twenty four day old seedlings were transplanted in the main filed in a randomized complete block design with three replications. The advanced rice line BU- 9958-40-5-1 was compared with BRRI dhan56, BRRI dhan57, Binadhan-7 and BU dhan1. Results showed that rice var. BRRI dhan57 matured earlier [81 days after transplanting (DAT)] while the advanced line took the maximum days (90 DAT) to mature in the field. Although the tallest plant (113.80 cm) was observed in BRRI dhan56 but tiller number (12.22), leaf area index (4.67) and dry matter production (398.69 g m-2) were the highest in advanced line BU-9958-40-5-1. The advanced line produced the highest grain yield (5.98 t ha-1) coupled with the highest biological yield (11.55 t ha-1) but failed to show the highest harvest index. Thus it seemed that this line was not much efficient in converting total dry matter into grain which is the ultimate target of crop production. Therefore, this result can help physiologists and breeders to determine physiological and morphological features of the advanced line BU-9958-40- 5-1 that contribute the most to increasing dry matter partition into grain.Bangladesh Agron. J. 2017, 20(2): 27-36